STRATEGI PENINGKATAN KETAHANAN PANGAN DINAS PERTANIAN DAN KETAHANAN PANGAN KOTA TANGERANG SELATAN - Rimadianti, Dini Maharani Arum; Daryanto, Arief; Baliwati, Yayuk Farida (Jurnal Gizi dan Pangan, 2016)
The objectives of this study were to analyze the food security condition, to analyze the external and internal factors that affect food security and to formulate strategies for improving food security in Tangerang Selatan. The primary data was collected by conducting a focus group discussion and questionnaire filling with purposive sampling technique. Descriptive method on secondary data such as food availability was used to analyze the food security condition. Internal Factor Evaluation (IFE) matrix and External Factor Evaluation (EFE) matrix were used to formulate strategies. Strengths, Weakness, Opportunities, and Threats (SWOT) matrix was used to determine the alternative strategies and Quantitative Strategic Planning Matrix (QSPM) was used to determine among feasible alternative strategies. The results showed that the most important internal factor is commitment of the regional leader and the most important external factor is geographical location of Tangerang Selatan. The total weighted score IFE matrix of 2.86 is average and EFE matrix of 2.81 is above the average. The SWOT matrix showed that the government of Tangerang Selatan may need to “improve food availability” because of “food price volatility”. The QSPM sum total attractiveness scores of 3.76 indicate that the government of Tangerang Selatan should “improve triple helix relations among university, industry, and government” as the strategy to improve food security in South Tangerang.Keywords: EFE matrix, food security, IFE matrix, QSPM, SWOT